Value Effect in Indonesian Stock Returns: The Implications for the Equity Mutual Fund Industry - Utomo, Samuel Kristanto; Tjandra, Kevin Antony (The Indonesian Capital Market Review, 2015)
We extend the persistence and pervasiveness of the presence of value effect to Indonesian stock returns in the last two decades by utilizing data set that is relatively free of survivor bias and selection bias. Our finding shows that value portfolios have been able to outperform growth portfolios. Furthermore, the presence of the effect as an asset pricing factor, along with the size effect, can significantly explain the returns of the aggregate equity mutual funds in Indonesia and unveil that the equity mutual fund industry does not provide sufficient risk-adjusted return to cover trading costs and fund expenses. Our proposition is that the equity mutual fund valuation will be better off to apply simpler model shown in this paper to capture the value premium as opposed to the general application of traditional valuation method.